Board experience in Mérida (Venezuela). 1808-1811 (2010)
The study focuses on the analysis of the establishing process of the conservative board of Fernando VII’s rights in Mérida. It was inspired by Caraca’s board, which was likewise the result of the Spanish regional boards. These boards granted the sovereignty over the people in the king’s absence. It is stated that Mérida board, on behalf of the people, welcomed Caracas’ proposal, with autonomic genuine vocation, got separated from Maracaibo province and turns to be a province. It organized its administration appointing its own authorities without breaking up ties with the monarchy to which it swore fidelity and respect. Likewise, the article goes over the accession process to the emereritense board of the urban centres which were part of Mérida old province.